Security-aware fair transmission scheme for 802.11 based cognitive IoT - Hayoung Oh (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Cognitive IoT is exponentially increased because of various real time and robust applications with sensor networks and big data analysis. Each IoT protocol of network layer can be RPL, COAP and so on based on IETF standards. But still collision problems and security-aware fair transmission on top of scalable IoT devices were not solved enough. In the open wireless LAN system based cognitive IoTs, IoT node that is continuously being stripped of its transmission opportunity will continue to accumulate packets to be sent in the butter and spoofing attacks will not allow the data transfer opportunities to be fair. Therefore, in this paper, we propose a method to reduce the average wait time of all packets in the system by dynamically controlling the contention window (CW) in a wireless LAN based cognitive IoT environment where there are nodes that do not have fair transmission opportunities due to spoofing attacks. Through the performance evaluation, we have proved that the proposed technique improves up to 80% in terms of various performance evaluation than the basic WLAN 802.11 based IoT.